PENGARUH MASSA KATALIS ZEOLIT ALAM PADA PROSES PIROLISIS LIMBAH PLASTIK LOW DENSITY POLYETHYLENE (LDPE) - Stephanus Danny Kurniawan; Harwin Saptoadi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Plastic wastes have considerable potential to be converted into alternative fuels through pyrolysis process and reduce negative impacts on the environment pollution. Plastic pyrolysis process carried out to obtain hydrocarbon compounds that can be used as fuel and increase the economic value of the plastic wastes. The raw material used is Low Density Polyethylene (LDPE). This study was conducted to determine the effect of variations in the mass of catalyst on the characteristics and applications of waste plastics pyrolysis oil (WPO). The reactor used was a batch-type fixed with a temperature of 450ºC, nitrogen flow rate of 0.8 l/min, which feedstock used is 2000gr and natural zeolite as a catalyst. The use of mass variation of Catalyst Feedstock Ratio (CFR) are 0.05, 0.10 and 0.15. The results showed that the increasing use of the mass of catalyst have an effect in decreasing of liquid products. Most liquid products obtained in the use of 100g catalyst, with a percentage of 56.75%wt liquid products, 38.60%wt gas products and 4.65%wt solid products. The results of the characteristics and properties testing of plastics pyrolysis oils include specific gravity, kinematic viscosity, flash point, pour point, cloud point, water content, ash content, carbon number distribution and PONA analysis showed that the pyrolysis oil has similarities with kerosene and diesel oil as well can be developed as analternative fuels.